Implementasi CNN Dan Haversine Formula Pada Pengembangan Sistem Absensi Karyawan Berbasis IOS - Rama Dwiyantara Perkasa; Oscar Hadikaryana (Journal Data Science, Technology, Informatics and Security, 2023)
This research aims to develop an iOS employee attendance system using Convolutional Neural Network (CNN) and the Haversine Formula. The study is conducted because traditional attendance systems often lack accuracy and efficiency. The research proposes the integration of CNN technology for employee face recognition and the Haversine Formula for calculating the radius of the location between the employee's position and the workplace. CNN is used to process employee face images through the iOS device's camera, thereby enhancing identification accuracy. The Haversine Formula calculates the distance from the current location to the workplace. The research results in an iOS mobile application for more efficient attendance management.